Positive Family Intervention for Severe Challenging Behavior I: A Multisite Randomized Clinical Trial. (July 2013) - Durand, V. Mark; Hieneman, Meme; Clarke, Shelley; Wang, Mo; Rinaldi, Melissa L.
The present study was a multisite randomized clinical trial assessing the effects of adding a cognitive-behavioral intervention to positive behavior support (PBS). Fifty-four families who met the criteria of (a) having a child with a developmental disability, (b) whose child displayed serious challenging behavior (e.g., aggression, self-injury, tantrums), and (c) who scored high on a measure of parental pessimism were randomly assigned to either PBS intervention or a combination of PBS and optimism training for parents (positive family intervention [PFI]). A manualized approach to both interventions was used for eight weekly individual sessions. Both groups improved in scores of parental pessimism as well as on standardized measures and direct observations of child challenging behavior. The PFI intervention resulted in significantly improved scores on the General Maladaptive Index of the Scales of Independent Behavior–Revised when compared with the PBS alone group. No differences in attrition were observed across the two different approaches. Importantly, significant improvements in child behavior at home were achieved through a clinic-based approach. Implications for working with families who may be less likely to benefit from parent training are discussed.